2018
DOI: 10.1038/s41586-018-0743-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural plasticity of D3–D14 ubiquitin ligase in strigolactone signalling

Abstract: SUMMARY The plant hormone strigolactones (SLs) regulate many aspects of plant physiology. In shoot branching inhibition, the SL-metabolizing α/β hydrolase D14 interacts with the F-box protein D3 to ubiquitinate and degrade the transcription repressor D53. Despite multiple modes of D14-SL interactions determined recently, how the hydrolase functions with D3 to mediate hormone-dependent D53 ubiquitination remains elusive. Here we show that D3 features a C-terminal α-helix (CTH), which can switch betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
186
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(200 citation statements)
references
References 39 publications
12
186
0
2
Order By: Relevance
“…However, recent findings demonstrated that specific binding of SL to D14 is enough to induce conformational change of D14 to interact with other components from the SL signaling pathway. [114][115][116] This model can explain why compounds like debranones (21), which lack the site of hydrolysis, are active SL agonists. Hydrolytic degradation of SLs by D14 may help maintain homeostatic level of SLs.…”
Section: Perception and Signal Transductionmentioning
confidence: 99%
“…However, recent findings demonstrated that specific binding of SL to D14 is enough to induce conformational change of D14 to interact with other components from the SL signaling pathway. [114][115][116] This model can explain why compounds like debranones (21), which lack the site of hydrolysis, are active SL agonists. Hydrolytic degradation of SLs by D14 may help maintain homeostatic level of SLs.…”
Section: Perception and Signal Transductionmentioning
confidence: 99%
“…A recent study has provided new insights into the formation of the rice D14-D53-SCF D3 complex (Shabek et al, 2018). The crystal structure of the D3-ASK1 complex revealed the Cterminal a-helix (CTH) of D3 is dynamic and exists in two forms, dislodged from, or engaged with the D3-ASK1 complex (Shabek et al, 2018). This D3-CTH peptide was shown to directly interact with D14 in vitro and in planta in a GR24-dependent manner (Shabek et al, 2018).…”
Section: Reviewmentioning
confidence: 99%
“…The crystal structure of the D3-ASK1 complex revealed the Cterminal a-helix (CTH) of D3 is dynamic and exists in two forms, dislodged from, or engaged with the D3-ASK1 complex (Shabek et al, 2018). This D3-CTH peptide was shown to directly interact with D14 in vitro and in planta in a GR24-dependent manner (Shabek et al, 2018). D3-CTH uses common residues to interact with both D3-ASK1 and D14, suggesting it binds to D14 when dislodged from D3-ASK1 (Shabek et al, 2018).…”
Section: Reviewmentioning
confidence: 99%
“…Biochemical analyses with recombinant D14 proteins by means of the synthetic SL analog GR24 revealed that the SL signal transduction requires GR24 cleavage 11,12 . One of the cleavage products, the D ring, may remain covalently attached to the receptor 13,14 , thereby probably allowing the recruitment of partners for downstream processes 15,16 . The required SL cleavage for signal transduction is still under debate 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the cleavage products, the D ring, may remain covalently attached to the receptor 13,14 , thereby probably allowing the recruitment of partners for downstream processes 15,16 . The required SL cleavage for signal transduction is still under debate 15,16 .…”
Section: Introductionmentioning
confidence: 99%